Does the Limit Order Routing Decision Matter? - Battalio, Robert; Greene, Jason; Hatch, Brian; Jennings, Robert (Review of Financial Studies, 2002)
We examine the impact deciding to route limit orders away from the New York Stock Exchange (NYSE) has on three dimensions of execution quality with methodologies controlling for market conditions and order submission strategies. Overall differences in limit order execution quality between regional stock exchanges and the NYSE are small, suggesting that the order routing decision may not affect retail limit order traders substantively. Conditioning on the distance between the limit order’s price and prevailing quotes, however, reveals systematic differences in execution quality. This implies that brokers can strategically route limit orders to improve retail limit order execution quality.